Relationship between Psychic distance, Business Networks and Opportunities in Internationalization Decision Making: A Case Study of Small High Technology, Knowledge-Intensive Firm. - SUEN, WING TUNG ARIEL (2012)
Abstract The convergence of the network perspective of the Internationalization Uppsala model (Schweizer et al., 2010) and the Psychic distance Theory (Smith et al., 2011) has created an interest in the relationship in between. The research is designed to explore a small high technology, knowledge-intensive firm’s behaviour on internationalization and network relationships, illustrated by a case study through a semi-structure, in-depth interview and by fitting the findings from the case study to the theories discussed in the literature, in particular to the conceptual framework which constitutes of the revised Uppsala model and Psychic distance Theory. An inductive approach is used, therefore, the study is presented from a broad picture of the field and further narrowed to a more specific topic.